EFEKTIVITAS BADAN USAHA MILIK DESA (BUMDesa) DALAM MENINGKATKAN PEMBERDAYAAN MASYARAKAT DI DESA CIREUNDEU KECAMATAN CILOGRANG - Deden Rahmat; Aah Tsamrotul Fuadah; Utang Rosyidin (STISIP Widyapuri Mandiri Sukabumi, 2022)
BUMDesa “Tirta Kahuripan” is the only Cireundeu Village Owned Enterprise which was established in 2016. In running its business. BUMDesa “Tirta Kahuripan” Cireundeu Village is engaged in drinking water packaging. The choice of this form of business was motivated by the existence of abundant springs in Cireundeu Village which, if used by the community, could increase the economic value. It is hoped that by improving the community's economy, it can have an impact on the improvement and quality of life of the local community. The results of research on the management of BUMDesa